Optimization of Cow’s Milk Processing into Milk Soap Bar on Small-Medium-Micro Enterprises (UMKM) - Ari Diana Susanti; Sulistyo Saputro; Wusana Agung Wibowo (Equilibrium Journal of Chemical Engineering, 2018)
The quality and quantity of cow’s milk produced were determined by the genetic, food, age, milking processing, and the treatment of cattle. The storability of fresh cow's milk tends to be short. Therefore, it is necessary to find ways to extend the life time of fresh cow's milk, one of which is by processing fresh cow's milk into other products, such as milk soap bar. The purpose of this study was to determine the appropriate method of milk soap bar production in home industries capacity and to formulate composition of vegetable oils and fresh cow's milk. The milk soap bar obtained then was analyzed in several laboratory tests such as acidity test (pH), moisture content, free alkaline content, and foam stability. Based on the research, it is turned out that the appropriate method of milk soap bar production was the cold process. The optimum formula is olive oil (11%), coconut oil (22%), palm oil (22%), fresh cow's milk (33%), and NaOH pellets (12% - equivalent to 9.2 N). The free alkaline content will decrease according the curing time. Simpler economic evaluation obtained that the production cost of milk was Rp.6,711.22/package of 80 grams of milk soap bar. Milk soap bar  is sold for Rp. 7,000.00 will provide 87.96% after-tax of ROI, 11.7– month of POT, and 65.31% of BEP.